In vitro antioxidant and antitubercular activity of Leucas marrubioides Desf. root extracts - A Gowrish, H.M Vagdevi, H Rajashekar (Journal of Applied Pharmaceutical Science, 2015)
Modern civilization is facing hundreds of disorders associated with free radicals. The natural antioxidants from non-edible plants are gaining importance to fight against these disorders. The intention of this study is to evaluate the petroleum ether, chloroform and methanol extracts of roots of Leucas marrubioides Desf. (Lamiaceae) for antioxidant and antitubercular activities. The antioxidant activity of the extracts has been evaluated using DPPH radical scavenging, reducing power and nitric oxide scavenging methods. The results of the study indicated that, methanol extract posses promising DPPH radical scavenging, reducing power and nitric oxide scavenging activity. The petroleum ether and chloroform extracts showed moderate antioxidant activity in all the three models. The antitubercular activity of all the extracts of L. marrubioides have been evaluated against Mycobacterium tuberculosis H73Rv strain using Microplate Alamar Blue Assay (MABA). The activity was documented within MIC range of 0.2 to 100µg/ml. The results of MABA showed that petroleum ether extract exhibited excellent antitubercular activity. The chloroform extract is moderately active, whereas methanol extract is less active against M. tuberculosis. The present investigation suggests that L. marrubioides posses remarkable antioxidant and antitubercular activity.
Keywords: Leucas marrubioides Desf., antioxidant activity, antitubercular activity, MABA.